152 Are neurophysiological parameters an objective measure of disease status and progression in primary progressive multiple sclerosis?. Issue 3 (9th February 2012) - Witherick, J; Kane, N; Butler, S; Walsh, P; Blake, K; Faulkner, H; Burrows, J; Inglis, K; Cottrell, D
Abstract : Background: Objective monitoring of disability progression is critical for any trial of novel agents in the treatment of multiple sclerosis. Currently, Kurtzke's Expanded Disability Status Scale (EDSS) is the most widely used marker of disease status. However there are significant problems with its use as a trial endpoint. Conventional MRI parameters are compromised by poor correlation with clinical disability and are not a measure of function. The development of a sensitive, objective and quantitative measure of function within the neural networks affected by MS, with detection of subclinical changes in small groups within short timeframes would be highly desirable. Multimodal evoked potential scores fulfil many of these criteria and have been shown to have clear correlation with clinical disability in a range of MS phenotypes. Our study is the first to measure serial global evoked potentials in a substantial PPMS cohort and this is the first interim analysis. Methods: A battery of evoked potentials including VEP, SSEP, BSAEP and MEP was recorded at 0, 6, and 12 months and a global evoked potential (GEP) score calculated using a consensus method. Clinical disability was measured using the EDSS and MSFC. Results: Twenty patients and three controls have completed the first year of the study. In cross-sectional analysis there was significant correlation between GEP score and EDSS at each time point (baseline [r=0.55; p=0.016], 6 months [r=0.72; p=0.0008], 12 months [r=0.59; p=0.0067]). There was also a correlation between MSFC and GEP on composite data analysis (r=−0.36; p=0.008). In longitudinal analysis there was no progression of the EDSS (Wilcoxon S=34.5; p=0.45) whereas we saw progression of GEP scores that approached statistical significance (S=13.5; p=0.02). Conclusions: GEP scoring shows significant promise in the search for accurate, sensitive and objective parameters of disease status in PPMS. Significant cross-sectional correlation with clinical disability and a suggestion of reliable and progressive deterioration with time needs to be expanded upon in the longitudinal analysis to be carried out in the following years of the study.